Sympatry Predicts Spot Pigmentation Patterns and Female Association Behavior in the Livebearing Fish Poeciliopsis baenschi. - Andrea J Roth-Monzón; Laura E Scott; Ashley A Camargo; Eliza I Clark; Eric E Schott; Jerald B Johnson (PLoS ONE, 2017)
In this study, we explored the possibility that differences in pigmentation patterns among populations of the fish Poeciliopsis baenschi were associated with the presence or absence of the closely related species P. turneri. If reproductive character displacement is responsible, spotting patterns in these two species should diverge in sympatry, but not allopatry. We predicted that female P. baenschi from sympatric sites should show a preference for associating with conspecifics vs. heterospecific males, but females from allopatric sites should show no such preferences. To evaluate these predictions, we compared spotting patterns and female association behaviors in populations of P. baenschi from Central Mexico. We found that both of our predictions were supported. Poeciliopsis baenschi that co-occured with P. turneri had spotting patterns significantly different than their counterparts from allopatric sites. Using a simultaneous choice test of video presentations of males, we also found that female P. baenschi from populations that co-occured with P. turneri spent significantly more time with males of their own species than with P. turneri males. In contrast, females from allopatric populations of P. baenschi showed no differences in the amount of time they spent with either conspecific or heterospecific males. Together, our results are consistent with the hypothesis that reproductive character displacement may be responsible for behavioral and spotting pattern differences in these populations of P. baenschi.